Pengaruh Kepemilikan Manajerial, Dewan Direksi, Kebijakan Dividen, dan Ukuran Perusahaan Terhadap Kinerja Keuangan (Studi Kasus Sektor Infastruktur Bumn di BEI Tahun 2020-2024) - Liza Zamili Tarigan; Asnahwati (ProBisnis : Jurnal Manajemen, 2025)
Financial performance as a determination of certain measures that can measure the success of a company in generating profits The assessment of a company's financial performance must be based on published financial data made in accordance with generally accepted financial accounting principles. The population used in this study is the population of state-owned enterprise infrastructure sub-sector companies that published complete financial reports for the period 2020 - 2024, totaling 8 companies listed on the Indonesia Stock Exchange. The sampling technique used in this study is the purposive sampling method, so the sample used in this study in state-owned enterprise infrastructure sub-sector companies that meet the criteria is 8 companies multiplied by the length of years, namely 5 years, so that the number of observations in this study is 40 observations. Based on the research conducted, partially Managerial Ownership and the Board of Directors do not have a negative and significant effect on financial performance, Dividend Policy, and Company Size have a significant effect on Financial Performance. Based on the results of the simultaneous test, Managerial Ownership (X1), Board of Directors (X2), Dividend Policy (X3) and Company Size (X4) on Financial Performance (Y) have a simultaneous effect.